Humic acid-like material from sewage sludge stimulates culture growth of ectomycorrhizal fungi in vitro - Hrselová, H; Soukupová, L; Gryndler, M (Folia microbiologica, 2007)
Significant effects of humic acid-like material (HALM) extracted from sewage sludge on dry matter production of cultures of ectomycorrhizal basidiomycetes were found in vitro. Mycelial growth of the majority of isolates tended to increase in the presence of the HALM and this effect was significant for 6 isolates. Strongest stimulation was observed in the case of Amanita muscaria, Leccinum aurantiacum and Lactarius deterrimus. The results suggest that the HALM can be used as an additive to media for cultivation of ectomycorrhizal basidiomycetes.
Keywords: Humic Substances; Mycorrhizae; Basidiomycota; Sewage; huminové látky; mycelium; mykorhiza; Mycelium; odpadní vody